Literature Review: Media Development Trends Augmented Reality IPA Elementary School 2020-2025 - Niniss Margareth; Arif Widiyatmoko; Bambang Subali; Nuni Widiarti (Publikasi Pendidikan, 2026)
In science education in elementary schools, students often have difficulty understanding abstract concepts, which leads to low motivation and poor learning outcomes. Therefore, innovative, interactive learning media that can visualize concepts concretely are needed. This study aims to examine trends in the development of augmented reality (AR) media in science education in elementary schools for the period 2020–2025. The method used was a Systematic Literature Review (SLR) with the help of Publish or Perish software connected to Google Scholar. From the initial 500 articles, a gradual selection was made based on the criteria of relevance, feasibility, and topic suitability, resulting in 22 articles being analyzed. The results of the study show that the trend of AR media development will increase significantly in 2024–2025, indicating a high level of interest among researchers in interactive technology-based media. AR media has been proven to be feasible and effective for use in science education because it can improve students' conceptual understanding, motivation, creativity, and learning outcomes, especially for abstract material. Additionally, various studies developed AR using the ADDIE model, Borg and Gall, and the Assemblr Edu platform to strengthen interactivity and practicality. In conclusion, AR-based learning media has great potential for implementation in elementary schools as a 21st-century learning innovation capable of addressing.